Novel compound heterozygous variants of SLC12A3 gene in a Chinese patient with Gitelman syndrome: a case report - Chen, Wenqing; Zhou, Qin; Chen, Hongjun; Li, Heng; Chen, Jianghua (Frontiers in Genetics, 2023)
Background: The Gitelman and Bartter syndromes are autosomal recessive disorders of renal tubular salt handling. Gitelman syndrome (GS) is characterized by hypokalemia, metabolic alkalosis, hypomagnesemia, hypocalciuria, and renin-angiotensin-aldosterone system (RAAS) activation, which is caused by mutations in the SLC12A3 gene. The disease gene of Bartter type IV, BSND, encodes barttin, an accessory subunit of a subclass of ClC channels. Although the clinical manifestations of the two diseases are similar, their gene mutation sites are different, therefore are considered as two distinct diseases. Case presentation: A 49-year-old man was admitted to our hospital due to muscular weakness. The patient's history revealed previous recurrent muscular weakness events associated with hypokalemia, featured by the lowest serum potassium value of 2.3 mmol/L. Whole-exome sequencing and Sanger sequencing were performed to explore the mutations of SLC12A3 gene in a GS pedigree. The reported male patient had persistent hypokalemia, hypocalciuria and normal blood pressure, without presenting obvious metabolic alkalosis, growth retardation, hypomagnesemia, hypochloremia or RAAS activation. A novel compound heterozygous mutation of the SLC12A3 gene (c.965-1_976delGCGGACATTTTTGinsACCGAAAATTTT in exon8 and c.1112T>C in exon9, and a heterozygous mutation of the BSND gene (c.318delC in exon3) were identified by genetic testing in the proband. Conclusions: This is the first study to report a novel pathogenic compound heterozygous mutation of the SLC12A3 gene and a heterozygous mutation of BSND in GS with an atypical phenotype. Such genetic studies could improve the diagnostic accuracy of GS. Meanwhile, further functional studies are required to investigate the pathophysiologic mechanisms of GS.